Failure Mechanism of Lithiophilic Sites in Composite Lithium Metal Anode under Practical Conditions - Zhan, Ying‐Xin; Shi, Peng; Ma, Xia‐Xia; Jin, Cheng‐Bin; Zhang, Qian‐Kui; Yang, Shi‐Jie; Li, Bo‐Quan; Zhang, Xue‐Qiang; Huang, Jia‐Qi (Advanced energy materials, 2022)
A 3D host decorated with lithiophilic sites has emerged as a promising strategy to stabilize lithium metal anode by guiding uniform Li deposition and relieving volume fluctuations. Herein, the evolution process of lithiophilic sites in a 3D host under practical conditions is disclosed in a typical system with metal‐based lithiophilic sites. Lithiophilic sites decreasing nucleation overpotential, however this effect gradually disappears during cycles under practical conditions. The significantly increased cycling capacity under practical conditions results in a rapid accumulation of dead Li compared with mild conditions. The dead Li covers the lithiophilic sites and blocks the diffusion channels of Li ions to the lithiophilic sites, failing to decrease the nucleation overpotentials. Once the dead Li has been removed after long cycles, the lithiophilic sites can still work. This work discloses the failure mechanism of lithiophilic sites and provides a guideline for designing lithiophilic hosts under practical conditions. The failure mechanism of lithiophilic sites in a 3D host under practical conditions is investigated. The advantage of lithiophilic sites, ie. decreasing the nucleation overpotential, gradually disappears during cycling under practical conditions. The rapid accumulation of dead Li covers lithiophilic sites and blocks the diffusion channels of Li ions to lithiophilic sites, inducing the disappearance of decreased nucleation overpotentials.